ChemInform Abstract: A Green, Facile Approach for the Multicomponent Synthesis of Bioactive Spiro[indoline‐3, 7′‐pyrrolo[1, 2‐c]imidazole] Derivatives. Issue 31 (August 2015) - Shen, Tianhua; Zhou, Yongbing; Che, Fengfeng; Yu, Jiangxia; Lin, Yan; Song, Qingbao
Abstract A variety of the title spiro‐compounds (IV) (17 examples) are synthesized via a NaHCO3‐catalyzed three‐component reaction.